Lightweight cryptography for security and privacy : 5th International Workshop, LightSec 2016, Aksaray, Turkey, September 21-22, 2016, Revised selected papers /: 5th International Workshop, LightSec 2016, Aksaray, Turkey, September 21-22, 2016, Revised selected papers. (2017) - Unknown
No abstract available